Evaluation of Fe3O4 incorporated functionalized carbon nanotube self-standing buckypaper as electrodes for solid-state symmetric supercapacitor - Bhaviripudi, Vijayabhaskara Rao; Dwivedi, Pravin K.; Pabba, Durga Prasad; Aepuru, Radhamanohar; Nakate, Umesh T.; Espinoza-Gonzalez, Rodrigo; Shelke, V, Manjusha (Journal of Energy Storage, 2023)
Iron (II, III) oxide and carbonaceous materials drawn considerable attention in energy storage owing to their special features. In this study, simple reverse co-precipitation, acid functionalization and vacuum filtration methods adopted to synthesis Fe3O4 nanoparticles of size 11 nm and -COOH acid functionalized multi-wall carbon nanotubes (FMWCNT). And further used them to prepare and optimize Fe3O4 in FMWCNT as 15 wt% and 25 wt% self-standing buckypapers of around 30-mu m thickness as electrodes for solid-state symmetric capacitor in the form of coin cell. The results show that 15 wt% and 25 wt% of Fe3O4-FMWCNT buckypapers hybrid nanostructures have Fe3O4 nanoparticles successfully incorporated in FMWCNT. The 25 wt% Fe3O4-FMWCNT electrodes with charge transfer resistance of 140 Ohm showed high areal specific capacitance (Cs) 78.5 mF/cm2 and retained 80 % of its Cs until 800 cycles even at high current density of 1 mA/cm2, scan rate of 100 mV/s whereas 15 wt% Fe3O4-FMWCNT showed low Cs of 47 mF/cm2 and retained 80 % of its Cs over 5000 cycles whereas only FMWCNT show Cs is 36 mF/cm2 with 54 Ohm. Finally, a solid-state symmetric supercapacitor coin cell with self-standing 25 wt% Fe3O4-FMWCNT buckypaper showed an excellent power density of 129.5 mW cm-3 and energy density of 3.6 mWh cm-3 is the innovation of the current work. This is mainly attributed to the combined effect of pseudocapacitive behavior from Fe3O4 by faradaic reaction with additional charge transfer resistance and electric double layer (EDLC) behavior from FMWCNTs by non-faradaic of electronic, ionic transport during charging-discharging. As-made solid-state symmetric supercapacitor appears as a high-performance storage device without extra support of current collectors for practical applications and for fabri-cation of planar capacitors.
Keywords: Buckypaper; Power density; specific capacitance; Symmetric supercapacitor